Relationship of stroke volume to different patterns of Cheyne-Stokes respiration in heart failure. Issue 4 (19th February 2019) - Inami, Toru; Kasai, Takatoshi; Yumino, Dai; Perger, Elisa; Alshaer, Hisham; Hummel, Richard; Lyons, Owen D; Floras, John S; Bradley, T Douglas
Abstract: Study Objectives: In patients with heart failure (HF) and reduced left ventricular ejection fraction (HFrEF), stroke volume (SV) falls during hyperpnea of Cheyne-Stokes respiration with central sleep apnea (CSR-CSA). We have identified two distinct patterns of hyperpnea: positive, in which end-expiratory lung volume (EELV) remains at or above functional residual capacity (FRC), and negative, in which EELV falls below FRC. The increase in expiratory intrathoracic pressure generated by the latter should have effects on the heart analogous to external chest compression. To test the hypotheses that in HFrEF patients, CSR-CSA with the negative pattern has an auto-resuscitation effect such that compared with the positive pattern, it is associated with a smaller fall in SV and a smaller increase in cardiac workload (product of heart rate and systolic blood pressure). Methods: In 15 consecutive HFrEF patients with CSR-CSA during polysomnography, hemodynamic data derived from digital photoplethysmography during positive and negative hyperpneas were compared. Results: Compared to the positive, negative hyperpneas were accompanied by reductions in the maximum and mean relative fall in SV of 30% ( p = 0.002) and 10% ( p = 0.031), respectively, and by reductions in the degree of increases in heart rate and rate pressure product during hyperpnea of 46% ( p < 0.001) and 13% ( p = 0.007), respectively. Conclusions: Our findings suggest the novel concept that the negative pattern of CSR-CSA may constitute a form of auto-resuscitation that acts as a compensatory mechanism to maintain SV in patients with severe HF.